PENGARUH DUKUNGAN ATASAN, KETERLIBATAN PENGGUNA SISTEM INFORMASI TERHADAP KEPUASAN PENGUNA SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER PADA LEMBAGA PERKREDITAN DESA DI KECAMATAN KEDIRI TABANAN - I Gusti Ayu Ratna Santiasih; Ni Wayan Yuniasih; I Putu Fery Karyada (Hita Akuntansi dan Keuangan, 2021)
Therphenomenon that occurs related to the financial institution in the villageplevel (LPD) in Bali, not many people want to accept and use IT-based information systems7, inmthencase of information system ITn-based today is a demand to support smooth operations. This3studylaimsktocdeterminevthegeffectkofjsuperiors support onnthelsatisfaction ofouserspofk computer-based accounting1informationpsystemshin the\LPD in Kediri subdistrict, Tabanan regency. To find out the effect of the involvement of information system users on user satisfaction of computer-based accounting information systems in LPD in Kediri sub-district Tabanan regency. The study was 52 people by using a purposive sampling method. Data collection uses a Likert scale questionnaire. Data analysis techniques by using multiple linear regression. The results showed that there is a positive and significant influence of superiors support on the satisfaction of users of computer-based accounting information systems at LPD in the sub-district of Kediri , Tabanan regency. And there is a positive and significant influence between the involvement of information system users on the satisfaction of users of computer-based accounting information systems at LPD at Kediri subdistrict, Tabanan regency. It is recommended to increase user satisfaction by increasing user involvement in system development, especially in user involvement in determining how to meet the information needed. And increased support from top management in the form of providing funds for system development.